Brønsted acid catalyzed remote C6 functionalization of 2,3-disubstituted indoles with β,γ-unsaturated α-ketoester - Zhang, You-Ya; Li, Lin; Zhang, Xiang-Zhi; Peng, Jin-Bao (Frontiers in Chemistry, 2022)
A metal-free catalytic approach for the remote C6-functionalization of 2,3-disubstituted indoles has been developed. In the presence of catalytic amounts of Brønsted acid, the β,γ-unsaturated α-ketoesters react with 2,3-disubstituted indoles at the C6 position selectively. Under mild reaction conditions, a range of C6-functionalized indoles were prepared with good yields and excellent regioselectivity. This methodology provides a concise and efficient route for the synthesis of C6-functionalized indole derivatives.